Corporate Environmental Disclosure in Practice: A Case Study of Indonesian Firms Under Regulatory Reform - Syah, Sultan; Abdulrahim, Mohamed Omar; Medya , Nova Dwi; Syah, Sri Rahayu (Jati: Jurnal Akuntansi Terapan Indonesia, 2026)
This study aims to understand the effects of carbon emission disclosure (CED) and PROPER on firm value and considers firm size, profitability, and leverage, before and after the implementation of POJK No. 51 of 2017. This study is quantitative and utilized secondary data sourced from PROPER, annual, and sustainability reports. The sample covered the 24 environmentally sensitive firms joining PROPER and were listed on the Indonesia Stock Exchange from 2010 to 2024. Longitudinal panel data regression (fixed or random effects) was employed to determine the most appropriate model. The findings uncovered that while regulatory changes seemed to successfully close the gaps in legitimacy for sustainability reporting, frameworks supporting self-regulation, like PROPER, did not significantly impact how investors view a firm. The government should improve and modernize regulations to support a market-based, environmentally sustainable approach. These results confirmed that disclosure measures affected how the market perceived an emerging market’s emissions transparency. From a practical perspective, it shows regulators, investors, and managers that mandatory reporting enhances corporate reputation and market confidence, whereas voluntary measures such as PROPER require more to be effective.